The political economy of urban food security in Sub-Saharan Africa - Maxwell, Daniel G. (International Food Policy Research Institute, 1998)
Sub-Saharan African cities in the late 1990s face a daunting set of problems including rapid growth, increasing poverty, deteriorating infrastructure, and inadequate capacity for service provision. However, even as a renewed debate is shaping up around issues of urban development, there is little attention given to the question of urban food security and nutrition. Whereas in the 1970s and 1980s, urban food problems in Africa commanded political attention, the nature of urban food insecurity in the 1990s is such that it has tended to lose political importance. This is largely because in the 1970s, the problem was one of outright food shortages and rapid price changes that affected large portions of the urban population simultaneously. The impact of structural adjustment, continued rapid growth, and an increase in urban poverty make food insecurity in the 1990s primarily a problem of access by the urban poor. Under circumstances where the urban poor spend a very large portion of their total income on food, urban poverty rapidly translates food insecurity. The lack of formal safety nets, and the shifting of responsibility for coping with food insecurity away from the state towards the individual and household level has tended to atomize and muffle any political response to this new urban food insecurity. This paper briefly reviews urban food insecurity and generates a set of empirical questions for an analysis of food and livelihood security in contemporary urban Sub-Saharan Africa, and then examines historical and contemporary evidence from Kampala, Uganda, and Accra, Ghana, to suggest some tentative conclusions.